Романовичі на стражі Холма - Масюк, Жанна Юріївна; Masjuk, Zhanna (Східноєвропейський національний університет, 2013)
У статті йдеться про функціонування літературних антропонімів Роман Мстиславович та Данило Романович у творчості Й. Г. Струцюка про Холмщину. У дослідженні розкрито функції та особливості конотативного наповнення цих імен, а також зроблено порівняльний аналіз екстралінгвальної інформації про денотатів в історичній літературі та досліджуваних творах. Roman Mstyslavich and Daniel Romanovic are the prominent figures in the Ukrainian national senses. They were the rulers of the principalities of Volhynia and Galicia and became one of the most powerful princes in east-central Europe. Also they were the founders of Cholm. Their rule was a golden era for this land. Wolhynian author J. Struciuk had written about Roman Mstyslavich and Daniel Romanovic dramatic dilogy «Roman and Romanovic», he had used these names in various poetry and novels. J. Struciuk has an original vision of contribution of these persons to the history. That is why literary anthroponyms Roman Mstyslavich and Daniel Romanovic had experienced some semantic transformation. This article discusses functions and connotations of literary anthroponym Roman Mstyslavich and Daniel Romanovic in J. Struciuk’s creations. The comparative analysis of extralingual information becomes one of the problems of this paper.
Roman Mstyslavich and Daniel Romanovic Were the Custodians Kholm
Keywords: денотат; літературний антропонім; онім; Романовичі; Холмщина; denotation; literary anthroponym; onym; Romanovic; Kholmshchyna